STUDY OF THE STATE OF LABOUR PROTECTION IN FOREIGN COUNTRIES WITH THE PURPOSE OF IMPLEMENTING ACHIEVEMENTS IN UKRAINE - Sierikov, Ya.; Sierikova, K.; Babishchuk, K.; Synelnikova, N. (Municipal economy of cities. Series: «Economy science», 2023)
The study provides statistical data on industrial injuries and occupational diseases in Ukraine and foreign countries. It presents the results of research on the state of labour protection in leading foreign countries. It also identifies achievements in labour protection in foreign countries, the implementation of which in the Ukrainian practice will reduce the level of industrial injuries and occupational diseases.